A disciplina de arte para o público alvo da Educação Especial: relato de professores - Padilha, Karina Garcia (Universidade Federal de São Carlos, 2022)
The present research aimed to study the analysis of the perception of the work of three teachers about the discipline 'Art', with teenagers Público Target of Special Education (PAEE) of basic education. The work was based initially in the bibliographic survey present in the Brazilian Digital Library of Theses and Dissertations (BDTD), on the basis of the Coordination for the Improvement of Higher Education Personnel (CAPES) and the Scientific Electronic Library Online (SciELO), using the terms “art and special education”, and “art and disability”, without restriction of year of publication, and eventually searched for words related, but unsuccessfully finding a large volume of searches within of the theme. There were only thirteen academic works, including theses and articles, otherwise. Thus, participants were selected for the research, making use of of the “Snowball Sampling” methodological technique, so that the choice of participants was performed according to each other's indications, forming a information chain. It is noteworthy that the three teachers had performances with students with disabilities aged between 12 and 18 years old. THE data collection instrument was a virtual interview, supported in a semi-structured interview script. The data from the teachers' speeches were transcribed and analyzed qualitatively, supported by the rationale of Vygotsky's cultural-historical approach. The categories of analysis focused were: Characterization of Participating Teachers; the formation of Art Teachers; the Human, Technological and Material Aids that these interviewed teachers use; and Organizational Culture. it is expected that the present study can mobilize more discussions about how it is being approached the work of the Art discipline with PAEE adolescents in basic education.
The subject of art for the target audience of special education: report of teachers
Keywords: Educação Especial; Professores; Arte; Inclusão; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO